Investigating the retention of Kokni lexicon among the youth of Cape Town's Kokni community - Mohamed, Naasirah (School of African and GenderStuds, Anth and Ling, 2020)
Originating in the Konkan coast of Maharashtra, India, a large group of people immigrated to South Africa. The migrations took place in the period of colonialism in the Cape and Natal, and sometimes extended into the later Union and Apartheid periods. These people have settled into living in Cape Town and could essentially be the largest Kokni group outside of India. Generations later, the language “Kokni” is still spoken (maintained) among the Kokni people. However, this is true for the elders, as they still maintain strong ties to India. The Kokni youngsters however have shifted away from the Kokni language as a result of the schooling system in which English and Afrikaans are dominant. Despite this, some youth still maintain various lexical items from the Kokni language in their everyday conversations in which English and Afrikaans are dominant. The study at hand set out to determine which Kokni lexicon (vocabulary) categories had survived and are still maintained among the post-shift generation of the Kokni youth, who now have English as their main language and Afrikaans as their second language. Additional emphasis was on determining whether gender, birth order, or grandparents in the home affects retention of the Kokni language lexicon (vocabulary). In order to do so, 40 Capetonians of Kokni descent, of both sexes between 18 to 35 years, born and raised in Cape Town, were recorded taking part in sociolinguistic interviews. The mixed-method approach was used to gather the background demographics and lexicon of the youth. Afterward, the data was organised and analysed using Guttman scaling; known as implicational scaling in Linguistics (Guttman, 1944; Babbie, 2011; Mesthrie, Chevalier & McLachlan, 2015). The data shows evidence of particular lexical categories being maintained more than others. Kinship terminology, typical food dishes, counting and every day vocabulary are among these aforementioned lexical categories. This confirms that the Kokni youth have shifted away from the language, toward English and Afrikaans, yet maintained some Kokni lexical categories.